An Analysis of Speaking Anxiety in Public Speaking Performance (RETAIN, 2022)
The common problem that often arises during public speaking is speaking anxiety among students. This triggers students’ understanding that public speaking is difficult to do. Therefore, this study was carried out to determine the existence of speaking anxiety among students and what factors trigger the emergence of speaking anxiety in public speaking. This study uses two types of instruments. The first is a questionnaire adapted from the Foreign Language Classroom Anxiety Scale (FLCAS). The questionnaire was used to obtain data on the existence of speaking anxiety in students. The data was taken from 47 students from the Excellent English Club (EEC) extracurricular at SMA Negeri 1 Babat, Lamongan. The second instrument is an interview, which is used to find out the factors that arise during public speaking. Based on the results of the study, the average score of the questionnaire shows that speaking anxiety belongs to an existing category when students do public speaking, and the results from interviews also show several factors, such as being afraid of making mistakes, having bad experience, and insecurity, that affect students’ performance when performing public speaking. The present study focuses on senior high students who are likely to have problems with their speaking anxiety during public speaking. Keywords: speaking anxiety, public speaking, EFL learners